PENDAMPINGAN PEMBUATAN TAMAN TEMATIK BERBASIS SUMBER PAKAN DI EKOWISATA LEBAH MADU “ROYAL HONEY” BANJAR SAKAH KECAMATAN SUKAWATI KABUPATEN GIANYAR - I Wayan Suanda; I Gusti Ayu Rai; Kadek Yuniari Suryatini; Dewa Made Alit; Kadek Intan Rusmayanthi (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2026)
Trigona sp. honey bee cultivation as a honey producer has grown quite rapidly after the 2019 COVID-19 pandemic. The Royal Honey Sakah honey bee ecotourism in Gianyar, established in 2017, has also grown rapidly with visitors from both foreign and local tourists. Providing plants as a source of bee food is a priority in Trigona sp. honey bee cultivation. Flowering plants as a source of honey bee food in this ecotourism area are still not comparable to houses (logs containing Trigona sp. honey bee colonies), especially during the prolonged rainy season which causes some plants to produce relatively few flowers. This condition requires the provision of flower plants based on food sources. in the honey bee ecotourism "Royal Honey" Sakah, Gianyar. This community service aims to assist in the creation of a thematic garden based on Trigona sp. honey bee food source plants. The creation of a thematic garden based on bee food sources can help provide food as a source of nectar for honey production. The management of the thematic garden is treated as organic plant cultivation. The concept of planting plants in the thematic garden is in the form of plant arrangement to give a natural, beautiful impression and the availability of food sources for honey bees. The arrangement of plants in green spaces, apart from being a source of food for bees, also has other functions, namely: production function, shade, education and research as well as conservation